Change Management and Student Admission Management in State Islamic Senior High Schools in Garut Regency - Moh Akmal Annas (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2026)
Organizational change has become an essential requirement for educational institutions seeking to maintain service quality amid technological advancement and growing public expectations. This study examined the relationship between change management and student admission management in State Islamic Senior High Schools with Skills Programs (Madrasah Aliyah Negeri Plus Keterampilan) in Garut Regency, Indonesia. A quantitative approach employing a descriptive correlational design was adopted. The sample consisted of 116 teachers and administrative personnel selected using the Slovin sampling formula. Data were collected through a validated and reliable five-point Likert questionnaire and analyzed using descriptive statistics, assumption testing, Pearson product–moment correlation, and the coefficient of determination. The findings revealed a positive and statistically significant relationship between change management and student admission management (p < .05), with a correlation coefficient of r = .647, indicating a strong association. The coefficient of determination (R² = .419) showed that change management explained 41.9% of the variance in student admission management, while the remaining 58.1% was influenced by other factors beyond this study. These findings demonstrate that effective change management strengthens the effectiveness of student admission management and supports organizational adaptability in Islamic secondary education.